Integrative transcriptomic and metabolomic analyses provide insights into the effects of overexpression and knockout of NtLHT1 in different tissues - Xing, Jiaxin; Wang, Wenyuan; Mi, Qili; Zhang, Lumin; Cheng, Changxin; Yang, Wenwu; Xu, Li; Jiang, Jiarui; Xiang, Haiying; Zeng, Wanli; He, Wei; Gao, Qian (Frontiers in Plant Science, 2026)
Lysine-Histidine Transporter 1 (LHT1) is a key amino acid transporter involved in plant nutrition, metabolism, leaf development, and abiotic stress tolerance. However, the regulatory mechanisms of NtLHT1 (LHT1 in Nicotiana tobacum) across different plant organs remain poorly understood. In this study, we utilized NtLHT1 knockout (LHT1-KO), overexpression (LHT1-OE), and wild-type (LHT1-WT) tobacco lines (cv. Honghuadajinyuan) to investigate the organ-specific effects of altered NtLHT1 expression on metabolic and transcriptomic profiles. At the 10-leaf stage, leaves, stems, and roots were collected for transcriptome sequencing (RNA-seq) and ultra-performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS)-based metabolomic analysis, with qRT-PCR performed to validate RNA-seq results. Principal component analysis (PCA) revealed that organ identity exerted a stronger regulatory influence on the metabolome and transcriptome than NtLHT1 genetic manipulation. LHT1-OE induced more profound metabolic and transcriptomic perturbations across organs compared to LHT1-KO: in roots, LHT1-OE upregulated pathways related to alkaloid biosynthesis and zeatin biosynthesis; in stems, it enhanced phenylpropanoid and terpenoid metabolic flux; in leaves, it repressed flavonoid and terpenoid biosynthesis by downregulating key structural genes (e.g., ACCT, FPPS, TPS) and modulated hormone homeostasis by increasing cytokinin (CTK) accumulation and decreasing auxin (IAA) and gibberellin (GA) levels. Collectively, our multi-omics analysis demonstrates that NtLHT1 acts as a “metabolic node” integrating primary and secondary metabolism as well as hormone signaling, exerting organ-specific regulatory effects on tobacco metabolism and gene expression. These findings provide a molecular framework for understanding NtLHT1’s multifunctional roles and offer potential targets for improving agronomic traits (e.g., leaf size, stress tolerance) in tobacco and other crops through genetic manipulation.